Pengaruh Promosi, Kualitas Produk dan Harga terhadap Keputusan Pembelian Konsumen pada Produk Scarlett Whitening - Sri Aderafika Sani; Maryam Batubara; Purnama Ramadani Silalahi; Rima Rizki Syahputri; Vega Liana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The purpose of this study was to determine the impact and impact of marketing on purchasing decisions, product quality on purchasing decisions, and the impact of pricing on purchasing decisions for Scarlett Whitening products, using a case study of UINSU students. Quantitative techniques are applied in this study. The population in this study consisted of all students of FEBI UINSU totaling 20,425 participants, with a sample group of 100 people. In this study, data were collected through a questionnaire. Validity test, reliability test, multiple regression test, hypothesis test, and coefficient of determination are all used in the data analysis approach of this research, which also includes the literature. Promotions have a huge impact on purchasing decisions, at least in part. Product quality has a large impact on purchasing decisions in part. time, pricing has no effect on purchasing decisions. Promotiion, product qualiity, and priice all have a big impact on UINSU students' purchasing decisions for Scarlett Whitening products. Keywords: Promotion; Product Quality; Price; Purchase Decision.